Instructing Practicing Physicians in Their Continuing Professional Development: A Survey of Canadian Health Sciences Librarians - Phinney, Jackie; Manley, Alison (Evidence Based Library and Information Practice, 2026)
Objective – Practicing physicians must engage in continuous learning throughout their careers, and in Canada this learning is guided by frameworks that include information retrieval and scholarship. Health sciences librarians (HSLs) are well equipped to support knowledge growth in this area through their demonstrated instruction capabilities. Yet the literature depicting librarian instruction of practicing physicians within the Canadian context is lacking, and an understanding of what characterizes their teaching to this learner group is needed.Methods – Using descriptive study design, a bilingual, electronic survey was distributed across two professional listservs for HSLs in North America in May 2024. Once the survey closed, data were cleaned and tabulated using Microsoft Excel and responses to open-ended questions were reviewed.Results – The survey engaged 21 respondents, and after data were cleaned, 15 were left for inclusion and analysis. Most worked in a hospital setting when teaching practicing physicians, and online synchronous delivery methods were most common, followed closely by in-person synchronous. A variety of topics were reportedly taught, and the use of formal objectives and feedback processes was common. In open-ended responses, participants suggested they may be interested in teaching practicing physicians about artificial intelligence.Conclusion – This study’s sample size is too small to offer definitive conclusions. However, it provides insight into what and how HSLs in Canada are teaching practicing physicians, and suggests missing components in planning instruction for this learner group. HSLs can provide value to Canadian physician organizations looking to bolster their CPD offerings and should advocate for themselves within their provincial and national networks.